Black History and Black Identity: A Call for a New Historiography - Wright, W. D. (Praeger, 2002)
Keywords: African Americans; Historiography; African Americans; Race identity; dept.his; faculty_collection

Competitive hagiography in biographies of al-Awzā'ī and Sufyān al-Thawrī - Judd, S.C. (Journal of the American Oriental Society, 2002)
The present paper examines how followers of 'Abd al-Rahcombining dot belowmān b. 'Amr al-Awzā'ī and Sufyān al-Thawrī tried to create boundaries between the nascent madhhabs that claimed them as eponyms. In the absence of significant differences in legal method, students turned to the two shaykhs' responses to the 'Abbāsid revolution to draw distinctions between them. The Arabic biographical sources contain stories of their responses to the revolution that reveal a dialogue between followers of the two shaykhs about the relative merits of their choices. The changing interpretations of their attitudes toward the 'Abbāsid regime and the exaggeration evident in the anecdotes examined have significant implications for our reading of medieval Arabic biographical sources.
1 citations (Crossref) [2023-10-31]
Keywords: dept.his

The pennsylvania state equal rights league and the northern black struggle for legal equality, 1864-1877 - Davis, Hugh (Pennsylvania Magazine of History and Biography, 2002)
Citation Key Alias: lens.org/021-378-663-485-819 tex.type: [object Object]
Keywords: dept.his; ⛔ No DOI found

Out of Africa - Feinberg, H.M.; Solodow, J.B. (Journal of African History, 2002)
This article traces the origins of the familiar quotation, 'there is always something new coming out of Africa'. It demonstrates that the phrase was a proverb that originated in Greece no later than the fourth century BC. It charts the transmission of the phrase from Aristotle to the twentieth century, noting that Erasmus is the most important link in the Renaissance and that he may be responsible for the current form in which the phrase is used. The article also shows that the meaning of the phrase was very different in ancient times from what it is today. Whereas 'something new' to Aristotle meant strange hybrid animals, current writers use the phrase with a sense of admiration.
9 citations (Crossref) [2023-10-31]
Keywords: Africa; Historiography; dept.his; dept.wll; history; perception; regional geography